Thermal Stability and Decay Resistance Properties of Tropical Wood Polymer Nanocomposites (WPNC) - Islam, M.S.; Hamdan, S.; Rusop, M.; Rahman, M.R. (Advanced Materials Research, 2013)
The effects of nanoclay on the thermal stability and decay resistance properties of tropical wood polymer nanocomposites (WPNCs) were investigated in this work. WPNC were prepared from several selected tropical wood species by impregnating the selected woods with a combination of nanoclay and phenol formaldehyde (PF) prepolymer mixture. The formation of WPNC was confirmed by the fourier transform infrared spectroscopy (FTIR) analysis. Thermal property of manufactured WPNC in terms of thermogravimetric analysis (TGA) was evaluated, and an improvement in thermal stability was found for fabricated WPNC. The wood was then exposed to two types of fungi; white-rot (polyporous versicolor) and brown-rot (postia placenta), for 12 weeks. Decay was assessed through percentage (%) of weight loss. A significant improvement was found in the treated woods compared to the untreated ones. In addition, the fabricated WPNC showed lower moisture content compared with raw one.